Pendampingan Kewirausahaan dalam Tema: “NGIPIK Sebagai Kelurahan Kampung Berdaya”, melalui Pengembangan Koperasi Srikandi Berbakti (Kelurahan Ngipik, Kecamatan Gresik) - Vembri Aulia Rahmi; Rini Puji Astutik; Umi Chotijah (Program Studi Manajemen Universitas Muhammadiyah Gresik, 2022)
The rapid development of industry triggers a reality that every region must have independence. Therefore, efforts to improve welfare continue to be carried out. One of the activities that can be done is entrepreneurship and cooperatives. The support of village officials and companies can also support the realization of regional independence. However, the reality on the ground as experienced by Kelurahan Ngipik, Kecamatan Gresik with products branded “Rosella Telaga Ngipik” and Cooperative Srikandi Berbakti” is actually different. There are weaknesses and imperfections in the implementation of business and cooperative operations. Motivation and skills that are not yet strong enough to be built in human resources can hinder the achievement of welfare. Lecture community methods, such as: demonstrations and discussions can improve the ability of business managers and cooperative administrators. Community activities went smoothly, namely: community service participants were able to understand entrepreneurship and digital marketing issue.